Topically applied novel TRPV1 receptor antagonist, ACD440 Gel, reduces evoked pain in healthy volunteers, a randomized, double‐blind, placebo‐controlled, crossover study - Segerdahl, M.; Rother, M.; Halldin, M. M.; Popescu, T.; Schaffler, K. (European journal of pain, 2024)
Background The TRPV1 receptor is a key molecule in pain generation. Previous development of oral TRPV1‐antagonists was halted due to systemic heat insensitivity and body temperature alterations. The present Phase 1b study investigated the efficacy, safety and plasma exposure of a topically administered TRPV1‐antagonist (ACD440 Gel) in healthy subjects. Methods The study comprised two parts. In part 1, 24 healthy subjects were included in this randomized double‐blind, placebo‐controlled, crossover trial. ACD440 Gel or Placebo was applied once daily and wiped off after 1 h, for 5 consecutive days. Assessments were done in normal skin, skin optimized for penetration (by stripping and occlusive gel application) and UVB‐irradiated skin. Pain induced by thermo‐nociceptive CO2 laser impulses generated laser‐evoked potentials (LEPs), with readouts of peak‐to‐peak (PtP) amplitude in vertex‐EEG and pain assessments by VAS (0–100). Endpoints include effects at 1 hour post‐dose, AUC(Days 1–5) and AUC(0–24, Day 4). In UVB‐irradiated skin, also pain on pinprick and skin redness were assessed. Part 2 explored the plasma pharmacokinetics of ACD440. Results ACD440 Gel reduced LEP PtP amplitude and VAS pain, p < 0.001, in all skin conditions, versus placebo. In UVB‐irradiated skin, pinprick pain was also reduced, p = 0.047. Effects were significant after 1 h, maintaining for at least 9 h. There were no adverse events or drug‐induced erythema. Plasma exposures of ACD440 were too low to establish an elimination half‐life of ACD400. Conclusions Topical ACD440 Gel demonstrated a significant analgesic effect on LEP, VAS score and pinprick pain, with low systemic exposures, supporting further clinical development. Significance This study demonstrates that the topical administration of a TRPV1‐antagonist, ACD440 Gel, has potential as a new treatment for painful conditions affecting the skin, such as chronic peripheral neuropathic pain, without any local or systemic side effects.